Final answer:
To write the given polynomials as a square of a binomial or as an expression opposite to a square of a binomial, we can factorize each polynomial.
Step-by-step explanation:
To write the given polynomials as a square of a binomial or as an expression opposite to a square of a binomial, we need to factorize the polynomial. Let's go through each polynomial:
A) 0.25x²–0.6xy +0.36y² = (0.5x - 0.6y)²
b)–a² +0.6a–0.09 = -(a - 0.3)²
c)9/16a⁴ +a³+ 4/9a² = (3/4a² + a)²
d)–16m²–24mn –9n² = -(4m + 3n)²